Metagenome sequencing and 103 microbial genomes from ballast water and sediments - Zhaozhao Xue; Yangchun Han; Wen Tian; Wei Zhang (Scientific Data, 2023)
Abstract The great threat of microbes carried by ballast water calls for figuring out the species composition of the ballast-tank microbial community, where the dark, cold, and anoxic tank environment might select special taxa. In this study, we reconstructed 103 metagenome-assembled genomes (MAGs), including 102 bacteria and one archaea, from four vessels on international voyages. Of these MAGs, 60 were ‘near complete’ (completeness >90%), 34 were >80% complete, and nine were >75% complete. Phylogenomic analysis revealed that over 70% (n = 74) of these MAGs represented new taxa at different taxonomical levels, including one order, three families, 12 genera, and 58 species. The species composition of these MAGs was most consistent with the previous reports, with the most abundant phyla being Proteobacteria (n = 69), Bacteroidota (n = 17), and Actinobacteriota (n = 7). These draft genomes provided novel data on species diversity and function in the ballast-tank microbial community, which will facilitate ballast water and sediments management.